Caeserian section and demografic factors in Muar Hospital, Johor , 1997 - Noorhaida Ujang; Hanafiah Mohd Salleh (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A pregnant mother who cannot deliver vaginally has to undergo caesarian section. Caesarian section is a process by which a baby is delivered via a cut through anterior abdominal wall and uterine wall. The objective of this exercise is to study the case series of caesarian section in Muar Hospital and to study its relationship with maternal sociodemografic factors such as ethnic, parity, socioeconomic factors, residence, height and weight gain as a predictors. A case-control study was carried out in Muar Hospital from June, 1996 till December, 1996. The target population was mothers who delivered f. at the hospital. Cases of 210 mothers who delivered by caesarian section were gathered with its control of 210 mothers delivered vaginally by frequency matching for age. Information gathered via treatment record kept at the Hospital Record Office. Study , showed that the most frequent caesarian section performed in the hospital was I emergency caesarian section (65.71%) as compared to elective (34.29%). The most frequent indication noted were repeat caesarian section ( 18.1% ) followed by fetal distress (13.81%) and disproportion (13.81%). Univariate analysis showed that there was no significant association between caesarian section with parity, ethnicity and education status. However, caesarian section was significantly associated with maternal working status, family income, residence, the status of antenatal care, height and weight gain. (p value <0.05). After controlling for confounder by multivariate analysis, caesarian section was found significantly associated to the status of antenatal care, residence, height and weight gain. (p < 0.05). Odds ratio for a pregnant lady to undergo caesarian section was 2.6 if she was to have poor antenatal care, 2.8 if she lived in town, 3.4 if she had a short stature of less than 145 cm and 88.9 if she gained weight more than 0.5 kg per week. Thus, antenatal care, maternal residence, height and weight gain may be used as a predictor for caesarian section in a pregnant lady. Steps must be taken by the health staff to improve the nutritional status of the children, so that malnutrition is really abated in the country .Malnutrition may lead to stunted growth. The health staff should improve the quality of antenatal care given as well as mothers should be motivated to participate as well. Mothers with weight gain problem should be given diet counseling. Therefore, a dietician is needed during an antenatal clinic session.